AKUNTABILITAS PENYELENGGARAAN PELAYANAN PUBLIK PEMERINTAH DI KANTOR KECAMATAN TAHUNA KABUPATEN KEPULAUAN SANGIHE - SASAUW, AMITHA; RORONG, ARIE; PALAR, NOVIE (JURNAL ADMINISTRASI PUBLIK, 2019)
Accountability The implementation of public services is a government effort to fulfillthe basic needs and civil rights of every citizen of the goods, services and administrative servicesprovided by public service providers. The purpose of this study was to determine the accountabilityof the Government Public Service in the District Office of Tahuna. , Sangihe Islands Regency, thetheory used is Accountability and Public Service. The research method used is the skinativemethod which is trying to find answers to questions related to the accountability of public servicedelivery. These questions require descriptive answers that describe the facts about the problemsinvestigated as well as rational interpretations of various field findings while analyzing all theconditions at the research site. Based on the results of research, namely the accountability of theimplementation of public services in the District Office of Tahuna, it is still not well implementedbecause the quality of apparatus / employee resources is inadequate, facilities and infrastructureto support the implementation of programs in the sub-district office are still lackingKeywords: Accountability Of Sub-distric Public Service